Effect of excess Mg to control corrosion in molten MgCl2 and KCl eutectic salt mixture. (January 2022) - Hanson, Kasey; Sankar, Krishna Moorthi; Weck, Philippe F.; Startt, Jacob K.; Dingreville, Remi; Deo, Chaitanya S.; Sugar, Joshua D.; Singh, Preet M.
Abstract: Structural alloys may experience corrosion when exposed to molten chloride salts due to selective dissolution of active alloying elements. One way to prevent this is to make the molten salt reducing. For the KCl + MgCl2 eutectic salt mixture, pure Mg can be added to achieve this. However, Mg can form intermetallic compounds with nickel at high temperatures, which may cause alloy embrittlement. This study shows that an optimum level of excess Mg could be added to the molten salt which will prevent corrosion of alloys like 316 H, while not forming any detectable Ni-Mg intermetallic phases on Ni-rich alloy surfaces. Highlights: Experimental results show that elemental Mg metal addition in molten MgCl2 -KCl salt can mitigate the corrosion of SS316H. Excess Mg addition, more than the amount required to react with salt impurities, can form Ni-Mg intermetallics in Ni-200. The optimum amount of Mg addition to avoid intermetallic formation would depend on the concentration of impurities in salt.